(untitled) (Revista de Estudos da Linguagem, 2004)
This paper presents a preliminary study of the emergence ofstructured variation in first language acquisition. We studied thespeech of 5 children aged 2:6 to 5 from the city of Rio de Janeiro.Our aim was to understand how children cope with variable inputin the acquisition of dative alternation in Brazilian Portuguese. Weassume that children’s variability is in part structured and is linkedto variability in adult speech. The results reveal that not all theavailable variants in the speech community are used in children’sperformance and that they tend to use the most frequent ones.